Performance analysis of BUNSD-LMA - Geaiger, Mohamed; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Elsheikh, Elsheikh Mohamed Ahmed (The International Association for Computer & Information Science, 2015)
The IETF is developed Network Mobility Basic Support (NEMO BSP) to support session continuity and reachability to the Mobile Network Nodes (MNNs) as one unit while they move. While NEMO move and attached to different networks, it needs to register the MNNs. This function of registration decreases the performance of NEMO. NEMO BSP suffers from some challenges. The most important of these challenges are route optimization, seamless mobility, handover latency and registration time. Binding Update No Sense Drop (BUNSD) Binding Cache Entry (BCE) in Local Mobility Anchor (LMA) is proposed to find a possible solution to MNNs. MNNs that are roaming in a Proxy Mobile IPv6 (PMIPv6) domain to perform seamless mobility while they are maintaining their session continuity through mobile router (MR). In this paper, BUNSD-LMA is analyzed mathematically with NEMO BS based on handover latency, total packet delivery delay cost, and throughput time during handoff. The analytical result shows that the BUNSD-LMA had better performance in term of handover, and registrations of MNNs. As a result the total packet loss is decreased and seamless mobility of MNNs enhanced compared to NEMO BS benchmarks. Keywords: NEMO, PMIPv6, BUNSD, MR, MAG, LMA